Inhomogeneous Broadening of the Exciton Band in Optical Absorption Spectra of InP/ZnS Nanocrystals - Savchenko, Sergey S. (Nanomaterials (Basel), 2019)
In this work, we have simulated the processes of broadening the first exciton band in optical absorption spectra (OA) for InP/ZnS ensembles of colloidal quantum dots (QDs). A phenomenological model has been proposed that takes into account the effects of the exciton–phonon interaction, and allows one to analyze the influence of the static and dynamic types of atomic disorder on the temperature changes in the spectral characteristics in question. To vary the degree of static disorder in the model system, we have used a parameter δ, which characterizes the QD dispersion in size over the ensemble. We have also calculated the temperature shifts of the maxima and changes in the half-width for the exciton peaks in single nanocrystals (δ = 0), as well as for the integrated OA bands in the QD ensembles with different values of δ = 0.6–17%. The simulation results and the OA spectra data measured for InP/ZnS nanocrystals of 2.1 nm (δ = 11.1%) and 2.3 nm (δ = 17.3%), are in good mutual agreement in the temperature range of 6.5 K–RT. It has been shown that the contribution of static disorder to the observed inhomogeneous broadening of the OA bands for the QDs at room temperature exceeds 90%. The computational experiments performed indicate that the temperature shift of the maximum for the integrated OA band coincides with that for the exciton peak in a single nanocrystal. In this case, a reliable estimate of the parameters of the fundamental exciton–phonon interaction can be made. Simultaneously, the values of the specified parameters, calculated from the temperature broadening of the OA spectra, can be significantly different from the true ones due to the effects of static atomic disorder in real QD ensembles.